Total syntheses of schulzeines B and C - Gurjar, Mukund K.; Pramanik, Chinmoy; Bhattasali, Debabrata; Ramana, Chepuri V.; Mohapatra, Debendra K. (Journal of Organic Chemistry, 2007)
Schulzeines B (2) and C (3) were synthesized by a convergent strategy using epimeric tricyclic lactam building blocks, 4 and 5, and the C28 fatty acid side chain 6. Syntheses of tricyclic lactams (4/5) were achieved by Bischler-Napieralski reaction. Sharpless asymmetric dihy-droxylation and BINAL-H-mediated asymmetric reduction of an enone was employed to prepare the key fatty acid side chain 6. The spectral as well as analytical data of 2 and 3 were in good agreement with the reported data for the natural products, thus confirming their assigned structures.
Keywords: Alpha-Glucosidase Inhibitors; Asymmetric Dihydroxylation; Adjuvant Activity; Pinellic Acid; Ketones; Reduction; Reagents; Configuration; Imbricatine; Alkaloids

Total synthesis and structural revision of stagonolide D - Vadhadiya, Paresh M.; Puranik, Vedavati G.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2012)
The total synthesis of the putative structure of stagonolide D has been completed. The relative and absolute configuration of stagonolide D was established by synthesizing its optical antipode. The adopted strategy involves the construction of the central macrolide employing ring-closing metathesis (RCM), followed by selective protecting group manipulations and a final concomitant −OTBS deprotection and displacement of an −OMs placed next to it, resulting in the formation of the epoxide ring.

Total synthesis of (–)-sacidumlignans B and D - Rout, Jeetendra Kumar; Ramana, Chepuri V. (Journal of Organic Chemistry, 2012)
The first total synthesis of naturally occurring sacidumlignans A (1), B (2), and D (4) was executed and the absolute configuration of 2 and 4 was determined. A diastereoselective α- methylation of a lactone was used as the key step for the control of the chiral centers of the central lignan core. An acid mediated dehydrative cyclization of an aldehyde to construct the dihydronaphthalene unit of 2 and the aromatization of the intermediate dihydronaphthalene derivative to synthesize 1 are the key reactions employed in this regard.

Total synthesis of the putative structure of xylarinol B - More, Atul A.; Ramana, Chepuri V. (Chemistry-An Asian Journal, 2014)
The total synthesis of the putative structure of xylarinolB is described and the need to revise its structure is demonstrated. The central benzoxepine skeleton was constructed by employing a cobalt-mediated bimolecular [2+2+2] Reppe-Vollhardt alkyne cycloaddition reaction.
Keywords: Chiral pool; cobalt; Natural products; structure elucidation; Total synthesis

Tuning the regioselectivity of gold-catalyzed internal nitroalkyne redox: a cycloisomerization and [3+2]-cycloaddition cascade for the construction of spiro-pseudoindoxyl skeleton - Kumar, Chepuri V. Suneel; Ramana, Chepuri V. (Organic Letters, 2014)
A simple domino process for the construction of the tricyclic core present in the spiro-pseudoindoxyl natural products has been developed. This involves two intramolecular events: the Au-catalyzed nitroalkyne redox leading to isatogen and its subsequent [3 + 2]-cycloaddition with a suitably positioned olefin. The option to modulate the size of the spiro-annulated ring, which is an important variable in this class of natural products, has been explored. Overall, this process molds a linear precursor into a tricyclic system with complete step, atom, and redox economy.

Target cum flexibility: synthesis of indolo[1,2-b]isoquinoline derivatives via cobalt-catalyzed [2+2+2] cyclotrimerization - Swami, Anuradha; Ramana, Chepuri V. (Synlett, 2015)
A modular approach for the synthesis of small molecules having the unnatural 6,11-dihydroindolo[1,2-b]isoquinoline tetracyclic core has been documented. An acid-catalyzed Friedel-Crafts-type C2-alkylation of N-propargyl indole with a suitably activated alkynol has been used to prepare the key indole-derived diynes. The cobalt-catalyzed [2+2+2] cyclotrimerization of these diynes has been studied with various internal/terminal alkynes and with nitriles.
Keywords: 2-b]-isoquinoline; cobalt; Indole; indolo[1; Pyridine; [2+2+2] cyclotrimerization

Total synthesis of (+)-petromyroxol - Mullapudi, Venkanna Babu; Ramana, Chepuri V. (Tetrahedron Letters, 2015)
The total synthesis of (+)-petromyroxol establishing its absolute configuration has been accomplished. The strategy developed employs easily accessible carbohydrate building blocks and comprises flexible and scalable chemistry that allowed the synthesis of (+)-petromyroxol along with its three diastereomers varying the stereochemistry mainly at C5 and/or C6. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Glucose diacetonide; Petromyroxol; Pheromone; Sea Lamprey; Total synthesis

Total synthesis of sinenside A - Vadhadiya, Paresh M.; Ramana, Chepuri V. (Organic Letters, 2015)
The first total synthesis of norlignan glucoside sinenside A has been accomplished. An intramolecular acetalization reaction has been employed as the key skeletal construct to forge the central cyclic disaccharide core. The trans-1,2-diol configuration present in the cyclic disaccharide of this natural product is unique and has been addressed by setting this configuration at the beginning. A 1,2-orthoester group has been selected as a handle for both sp glycosidation and for differentiation of the C2'-OH (that participates in the key acetalization reaction) of the sugar unit.

Total synthesis and structural assignment of hexaketide xylarinolb and its C1-epimer - Mullapudi, Venkanna Babu; Ramana, Chepuri V. (Asian Journal of Organic Chemistry, 2016)
The total synthesis of two isomeric hexaketides isolated along with sordarial, which have the proposed relative arabino and ribo configurations, has been executed. A Rh-catalyzed [2+2+2]-alkyne cyclotrimerization has been employed as the key reaction to construct the central dihydroisobenzofuran core. The absolute configuration of the xylarinolB hexaketide has been established as l-arabino. This is the first natural product of this family for which the absolute configuration has been determined, and this can be extended to provide structural details of several of related hexaketides.
Keywords: hexaketides; sordarial; Wilkinson's catalyst; xylarinolB; {[2+2+2]-cyclotrimerization

Total synthesis of integrastatin B enabled by a benzofuran oxidative dearomatization cascade - More, Atul A.; Ramana, Chepuri V. (Organic Letters, 2016)
The first total synthesis of integrastatin B, a potent HIV-1 integrase inhibitor, has been accomplished in seven steps with a 17.9% overall yield employing easily accessible starting compounds. The Oxone-mediated oxidative benzofuran dearomatization cascade has been employed as the key skeletal construct to forge the central tetracyclic nucleus.

Total synthesis of (+/-)-allocolchicine and its analogues using Co-catalyzed alkyne [2 - Paymode, Dinesh J.; Ramana, Chepuri V. (ACS Omega, 2017)
The total synthesis of (+/-)-allocolchicine has been completed by employing cobalt-catalyzed alkyne [2 + 2 + 2]-cyclotrimerization as the key reaction. The essential diyne has been synthesized from easily available 3,4,5-trimethoxybenzaldehyde following simple chemical transformations. In general, the cycloaddition gave a mixture of C(9) and C(10) isomers thus allowing the synthesis of both allocolchicine and its C(10)-carboxylate. Because this cycloaddition was employed at the penultimate stage, it allowed the synthesis of various analogues having the diverse functionality at C(9) and/or C(10) of ring C.

Total synthesis of propolisbenzofuran B - Srinivas, Kolluru; Ramana, Chepuri V. (Organic Letters, 2017)
An efficient synthesis of propolisbenzofuran B, which possesses promising anticancer activity, is reported. The key cyclohexanone framework of this tricyclic natural product has been constructed employing a Rh-catalyzed intramolecular olefin hydroacylation. The requisite key olefin intermediate was synthesized by using gold-catalyzed allenyl ether [1,3] O -> C rearrangement.

Total synthesis of notoryne - Senapati, Sibadatta; Das, Shyamsundar; Ramana, Chepuri V. (Journal of Organic Chemistry, 2018)
The structure of notoryne comprises a halogenated 2,2'-bifuranyl moiety along with a terminal cis-enyne unit. In this work, we document the first total synthesis of notoryne, confirming its assigned relative and absolute configurations. The devised route comprises a glucose diacetonide-derived chiral pool intermediate as the starting point and 5-endo bromo-etherification for making the key bis-furan unit, anomeric C-allylation, as well as a relay cross-metathesis to install the cis-enyne unit.

Total synthesis of (+)-petromyroxol (vol 56, pg 3933, 2015) - Mullapudi, Venkannababu; Ramana, Chepuri V. (Tetrahedron Letters, 2020)

Total synthesis of the pseudoindoxyl class of natural products - Dhote, Pawan S.; Patel, Pitambar; Vanka, Kumar; Ramana, Chepuri V. (Organic & Biomolecular Chemistry, 2021)
The pseudoindoxyl sub-structural motif, amongst the large set of the indole class of alkaloids, represents a unique subset of the oxygenated indole class of the alkaloid family. A majority of this class of natural products contains complex bridged/polycyclic scaffolds with interesting biological profiles. They are thus attractive synthetic targets. Starting from 1963, twenty-eight natural products having the pseudoindoxyl scaffold have been isolated, among which the synthesis of 13 natural products has been accomplished. In this review, we highlight the completed as well as the formal total synthesis of the natural products with a spiro-pseudoindoxyl ring, with a focus on their development. The challenges and the future perspective based on the recent developments in the field will also be discussed. We strongly believe that this review will not only update but also attract the attention of researchers in dealing with the synthesis of pseudoindoxyl compounds.

Total synthesis of (-) and (+)-zingibergingerols A - Shet, Manoj N.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2024)
The first total synthesis of both of the enantiomers of Zingibergingerol A has been accomplished. The distinctive 3,7,9-trioxabicyclo[4.2.1]nonane skeleton is crafted through gold-catalyzed alkynol cycloisomerization. The synthesis comprises sequential C-C bond formations at both ends of epichlorohydrin: first opening the epoxide with eugenol-derived alkyne, followed by subsequent epoxide installation, and again opening with a Grignard reagent. The resulting alkynol with a fixed C5 stereochemistry was subjected to O-allylation, followed by dihydroxylation and alkynol cycloisomerization.

Total synthesis of (±)-streptoglyceride A and of putative (±)-streptoglyceride C - Khobragade, Virendra R.; Ramana, Chepuri V. (Organic Letters, 2025)
The first total synthesis of (+/-)-Streptoglyceride A-one of the early members of this family to be isolated-has been accomplished, along with the synthesis of the putative structure of (+/-)-Streptoglyceride C. The unique tricyclic ring present in these natural products has been constructed by employing a gold-catalyzed tandem diynol cycloisomerization followed by one-pot dihydroxylation/trans-glycosylation. The pendant diene unit was fabricated by Takai olefination and subsequent Stille coupling.

Total synthesis of lucidimines/ganocalicines A/B, sinensine E, and ganocochlearine E - Sai, Godi Kiran Venkata; Ramana, Chepuri V. (Organic Letters, 2026)
The central tetracyclic framework shared by the Ganoderma alkaloids-lucidimines/ganocaclicines A and B, sinensine E, and ganocochlearine E-appears inherently predisposed to arise from a diyne-nitrile cyclotrimerization event. A Co(I)-catalyzed intramolecular [2 + 2 + 2]-alkynenitrile cyclotrimerization has been employed to accomplish the first racemic and enantioselective total syntheses of sinensine E, lucidimine A, and ganocochlearine E, thereby establishing/revising their assigned stereochemical structures.